El libro de los pequeños milagros ... - Muñoz Rengel, Juan Jacinto, 1974- (Voces (Madrid, Spain), 2016)
Part bestiary, part theology manual, part science fiction, part catalog of wonders--this collection of one hundred micronarratives chronicles various entities and events spanning from the city to outer space.